Perangkat Lunak Pengkonversi Teks ke Tulisan Aksara Batak Mandailing (Text Convertion Software to Batak Mandailing Aksara Script) - Mei Lina Fianti; Fazmah Arif Y.; Muhammad Zuliansyah (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2004)
Text convertion to Batak Mandailing Script is a software to convert a common textinto Batak Mandailing Script written. Text convertion process is merge of letters in BatakMandailing Script. Before a sentence able to written in Batak Mandailing Script, it have toseparated into words that arranged the sentence in a text processing module. Then the wordsseparated into its arranged root words. From the root words the system will be seek thesuitable script to show on the screen.Searching toward the suitable script must be done considering the written rules of aletter may differ following the condition when it transform into the script. It also more flexiblethan consider root words as smallest units which will have more combination. Moreover, bymerging the suitable script, stored script data will be smaller. Digital script data will bestored in Batak Mandailing Script files.Text processing module consist of few parts. The Parts designed by following the stepsfound in Compilation technique by concerning text transform into Batak Mandailing Scriptthat usually done. Among the parts is lexical analyzer which separated the sentence intowords, syntax analyzer to separated words into root words, semantics analyzer to separatedroot words into set of the semantics which aim to draw near it to code generator., and it willbe written by code executor into Batak Mandailing Script.Depending on the trial obtained a conclusion that the software capable to convert acommon text into Batak Mandailing Script. Every test that had been done is fit with ”how towrite Batak Mandailing Script”.Keywords: convertion text ,batak mandailing script.